Implementasi Lean Sigma untuk Menciptakan Lingkungan Kerja Bebas Insiden di Dept. Treat & Ship PT. CPI Duri – Riau - zayyinul hayati zen (Jurnal Surya Teknika, 2016)
In effort to build incident free operations at workplaces of Treat & Ship Department PT.Chevron Pacific Indonesia–Duri Riau, Leadership Team had to perform several efforts in many aspects. In order to focus those efforts which were performed by Leadership Team to build incident free operations at workplaces, Lean Sigma method was implemented to deliver several recommendations capturing all aspects to be focused by Leadership Team which need to be implemented to achieve better performance in Health, Environment, and Safety in order to build incident free operations at workplaces. On 2013-2014, there were 165 Nearmiss occurrences or 83 Nearmiss occurrences per year which those Nearmisses occurrences would potential to create incidents, such as: day away from work, injury, motor vehicle crash, oil spill, and fire. In this research identified root causes of Nearmiss occurences which potential to create incident, root causes identification done based on “procedure and safe work practices” and “design” category by using “Fishbone” method. Systematic recommendations were obtained to focus Leadership Team efforts in order to build incident free operations at workplaces, which those recommendations consist of 18 solutions. By implementing the systematic solutions recommended to Leadership Team in order to reduce and eliminate Nearmiss occurrences also to build incident free operations at workplaces in Treat & Ship Department of PT.Chevron Pacific Indonesia–Duri Riau, it had obtained improvement results in Nearmiss occurrences which these achievements should be maintained and improved. The improvement results were Nearmiss occurrences decreased 98% from 83 Nearmiss occurrences per year on 2013-2014 became 2 Nearmiss occurrences per year on 2015 in Treat & Ship Department of PT.Chevron Pacific Indonesia–Duri Riau with financial benefit as much Rp.688,000,000 per year.